Pemberdayaan UMKM Melalui Digitalisasi Keuangan Menggunakan Aplikasi SI APIK di Desa Torosiaje, Kab. Pohuwato, Gorontalo - Muhammad Ardi; Wahyudi Rusdi; Ikrima Usman; Ummu Ainun; Hajrahwati Tahir (Komunal Jurnal Pengabdian Masyarakat, 2023)
Torosiaje Village is a 'floating' village which is one of the tourist destinations in Pohuwato Regency, Gorontalo. This uniqueness causes the UMKMs that develop there to be dominated by UMKMs engaged in tourism and culinary. However, the problem is that almost all of these UMKMs are not yet digital-based in their financial management, everything is still manual-based, from bookkeeping to marketing. SI APIK is an Android-based financial application that aims to improve access to finance, encourage UMKMs to upgrade, and encourage the productivity of UMKSs themselves. Therefore we feel the need to provide training/outreach to the community in Torosiaje village regarding Financial Digitalization in UMKM governance, with the hope of increasing UMKM actors' understanding of the importance of digitizing finance using the SI APIK application in every financial activity starting from simple bookkeeping, financial services access to finance, organizational management, business legality and digital financial records.